Pancreatic Islets: Functionalization of Alginate with Extracellular Matrix Peptides Enhances Viability and Function of Encapsulated Porcine Islets (Adv. Healthcare Mater. 9/2020). Issue 9 (6th May 2020) - Medina, Juan D.; Alexander, Michael; Hunckler, Michael D.; Fernández‐Yagüe, Marc A.; Coronel, María M.; Smink, Alexandra M.; Lakey, Jonathan R.; de Vos, Paul; García, Andrés J.
Abstract : Interactions between pancreatic islets and extracellular matrix (ECM) have regulative effects on pancreatic islet survival and function. These interactions are lost during the islet isolation process necessary for islet transplantation. In article number 2000102, Jonathan R. Lakey, Paul de Vos, Andrés J. García, and co‐workers show that incorporation of a specific adhesion peptide sequence promotes islet health and function in vitro. The cover image shows a healthy pancreas (top), which is digested to extract islets. Isolation results in islet damage, evidenced by their necrotic core and loss of adhesion substrate (middle). Encapsulation of isolated islets into biomimetic microcapsules restores islet‐adhesion connections and enhances the islet's health and function (bottom).